DEVELOPMENT OF VALUE AND SENSE CONSCIOUSNESS OF JUNIOR SCHOOLCHILDREN IN MATHEMATICS LESSONS - Mayborodyuk, N.D. (Pedagogy of Higher and Secondary Education, 2010)
In the articles demonstration experimental material of pedagogical model of the personality oriented lesson opens up on development of valuable-semantic consciousness ofpupils ofprimary classes on the lessons of mathematics.